Determinants Of Financial Performance Of Local Governments In Bali Province: The Role Of Financial And Human Capital Aspects - Dewi, Nyoman Ayu Wulan Trisna; Wiguna, I Gd Nandra Hary (Vokasi : Jurnal Riset Akuntansi, 2024)
This research aims to examine the influence of financial factors sourced from internal (Local Revenue) and external (Intergovernmental Revenue) as well as the aspect of human resources in the form of value-added human capital on the financial performance of the local government in Bali Province. This study uses a quantitative research method with a correlational research approach. The population in this study is the financial reports of the Provincial Government of Bali. This research uses secondary data from the Regional Government Budget (APBD) of the District/City Governments in Bali Province from 2019-2023 obtained from dpjk.kemenkeu.go.id. This study employs a multiple linear regression analysis approach. The research results show that financial factors sourced from internal (Local Revenue) and external (intergovernmental revenue) as well as the aspect of human resources in the form of value-added human capital have a significant impact on the financial performance of local government. This research is limited to examining only the financial and human capital aspects. The findings of this research are expected to provide policy recommendations for local governments in optimizing regional financial management. Examining financial factors sourced from internal and external sources as well as human capital factors.